2018
DOI: 10.37706/ijaz.v3i3.92
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Palm Farmers’ Decisions to Dispense Plantage-Product Zakat in Labuhanbatu Selatan Regency

Abstract: Zakat is one of the five points in rukun Islam and consists of two types: zakat nafs (soul) and zakat maal (wealth). One of the many kinds of zakat maal is plantage-product zakat. Labuhanbatu Selatan Regency is an area that contains 160,785.04 hectares of palm plantation land as recorded in 2016. The area also produced 7,493,696.18 tons of Fresh Fruit Bunches (FFB) in the same year. The objective of this study is to identify the potential of plantage-product zakat (specifically palm plantage) and analyze the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Understanding is the realization of knowledge that was watched and listened to by someone intently. Based on the study of Syn et al (2018), understanding zakah influenced the farmers' intention to pay zakah. Asmalia et al (2018) showed that understanding influences the attitude then attitude would force the intention of people to pay zakah.…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding is the realization of knowledge that was watched and listened to by someone intently. Based on the study of Syn et al (2018), understanding zakah influenced the farmers' intention to pay zakah. Asmalia et al (2018) showed that understanding influences the attitude then attitude would force the intention of people to pay zakah.…”
Section: Hypothesesmentioning
confidence: 99%
“…Paying zakah is obligatory for every Muslim who has fulfilled the nishab provisions (Amalia & Mahalli, 2012). There are two types of zakah, namely zakah nafs (fitrah/soul), which is mandatory to be given out at the end of Ramadhan, and zakah maal (wealth), which includes business revenue, wages/salaries, mining, agriculture, marine products, farming, plantation product, treasure, gold and silver which have it is own nishab each type of zakah (Syn et al, 2018). For the specific discussion, this study focused on one sector, agricultural zakah.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation